Incidence and Outcomes of Postoperative Atrial Fibrillation After Left Ventricular Assist Device. Issue 5 (September 2018) - Deshmukh, Amrish; Bhatia, Ankit; Anyanwu, Emeka; Ota, Takeyoshi; Jeevanandam, Valluvan; Uriel, Nir; Tung, Roderick; Ozcan, Cevher
Abstract : This study sought to determine the incidence, predictors, and outcomes of postoperative atrial fibrillation (POAF) in patients undergoing implantation of left ventricular assist devices (LVADs). A retrospective analysis of all patients who underwent LVAD implantation from 2013 to 2014 was conducted. Postoperative AF, survival, and thrombotic complications were evaluated after surgery. A total of 47 patients (mean age, 56.4 ± 12.5 years; 33 male) were included and followed for a median of 331 days. Within 30 days of surgery, 13 (28%) patients developed POAF at mean 7.9 ± 8.5 days. Obstructive lung disease was a predictor of POAF ( p = 0.01). Postoperative AF was not associated with increased mortality, length of stay, or thrombotic complication within 30 days. Postoperative AF was predictive of recurrent new AF (24 vs. 5.5%) after 30 days of LVAD implantation. Also, POAF was associated with increased risk of ischemic stroke and device thrombosis during follow-up ( p = 0.01). These results show that unlike in other cardiac surgery, POAF does not have a negative impact on early postoperative morbidity or mortality. However, POAF is a predictor for future AF, ischemic stroke, and device thrombosis.